2007
DOI: 10.1037/1053-0797.17.4.208
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome of dream work for East Asian volunteer clients: Dream factors, attachment anxiety, Asian values, and therapist input.

Abstract: Eighty-eight East Asian volunteers were paired with 6 East Asian therapists who provided low or high input in single-dream sessions. Volunteer clients with poor initial functioning on the target problem associated with their dreams and high self-efficacy for working with dreams profited more from dream sessions than did their counterparts. Although no main effects were found for therapist input, volunteer clients who scored higher on attachment anxiety had better outcome in the low-input condition, whereas cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 44 publications
(61 reference statements)
4
21
2
Order By: Relevance
“…Their relationships with cousins, nephews, aunts, uncles, and/or grandparents during their early childhood also greatly influenced their personal development. Hill et al (2007) asserted that it is important to explore the relationship between the interpersonal content of dreams and its effects on the process and outcome of dream work. We found that for college students in Taiwan dream analysis elicited dreams with considerable interpersonal contents.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Their relationships with cousins, nephews, aunts, uncles, and/or grandparents during their early childhood also greatly influenced their personal development. Hill et al (2007) asserted that it is important to explore the relationship between the interpersonal content of dreams and its effects on the process and outcome of dream work. We found that for college students in Taiwan dream analysis elicited dreams with considerable interpersonal contents.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Hill et al (2007) indicated that evidence has pointed to the three-stage dream model as being effective in terms of client's evaluations of sessions, insight gained into the discussed dream, and gains in action ideas related to the discussed dream, there are still many unknowns about how the model works. Given this background, the purpose of the current study was to examine the content of helpful components involved in Hill's dream work model from the judge's comprehensive viewpoint.…”
Section: Purpose Of the Present Studymentioning
confidence: 97%
See 2 more Smart Citations
“…The goal of exploring associations is to assist the child in uncovering salient affective and cognitive elements in the dream scene and to formulate potential meaning conveyed through each object. Studies indicate that exploring associations with objects in the dream scene may uncover difficulties that exist in the dreamers' interpersonal relationships and family environment; themes that are common to dream work (Hill et al, 2007;Tien, Linn, & Chen, 2006).…”
Section: Explore Associations With Objectmentioning
confidence: 99%